COVID-19 Pandemic and Sectoral Stock Performance in Nigeria: A Quantile Regression Approach (2021)
This study examines the effects of COVID-19 pandemic (cases and deaths) and government policy responses on the sectoral stock returns in Nigerian using daily data from January 2nd, 2020 to November 24th, 2020. The stock returns of five sectors are considered which include consumer goods, banking, oil and gas, food/beverages and insurance. Employing OLS and quantile regression methods, our results establish that COVID-19 cases, deaths, and government stringency, and containment and health policy have strong impacts on sectoral stock returns. However, the impact appears to be stronger from COVID-19 confirmed cases, and containment and health policy than from its deaths and government stringency policy. Structure of dependence is predominantly stronger in the bearish markets and is significantly negative at the extreme lower and intermediate quantiles. COVID-19 cases and stringency and containment and health policies move in opposite direction to these sectors’ stock returns. As Coronavirus cases surge, stock prices decline.